IMPROVING YOUNG LEARNERS’ SPEAKING SKILL THROUGH CULTURAL-BASED MUSICAL MINI-DRAMA - Eko Heriyanto (Universitas Aki, 2018)
Nowadays, in our country, many several issues have come up to the public such as violence, sexual crime, corruption, vandalism, mass fight, juvenile delinquency, economic and politic problems, and so on. The government needs to overcome them in order to create a better condition of life. There are so many ways to do which can reduce these problem. One of them is through education. Education is considered as an alternative way to overcome, at least, to reduce these issues. Definitely, it should be begun from the early education. Young learners are the best age to be given a good education in line with their ages. It is through musical cultural mini-drama. They will learn easily on English speaking through this strategy. Besides improving their speaking skill, it will make shape their good character through the values of the songs. The research used descriptive qualitative and quantitative design by using SPSS. The object this research were seventeen students of Elementary School in Semarang. The assessment instrument used speaking rubric/table score, progress checking form, and behavior development checklist. The results were (1) CMMD could be implemented by using the steps of preparation, implementation, and assessment. In each of steps, students learned much more about speaking. Not only vocabulary, pronunciation, expressions, but also the valuable cultures to shape their behaviors. Some students had pronunciation and expression difficulties, but it could be overcome by practicing a lot. (2) CMMD is one of effective strategies to improve students’ speaking skill based on the result of the SPSS analysis which showed the null hypotheses were sig. of 0.000. It means that this strategy is effective to be used.